Probing Experiential Learning Approach in Islamic Religious Education - Hanif Cahyo Adi Kistoro; Eva Latipah; Norhapizah Mohd Burhan (Jurnal Pendidikan Islam, 2023)
This study delves into the effective strategies employed in Islamic religious education to illuminate the nexus between instructional approaches and subject matter alignment. Utilizing a qualitative research methodology with a phenomenological orientation, the investigation involved fifteen high school Islamic religious education teachers. Participants were selected using a purposive technique, focusing on eligibility criteria specific to Islamic religious education instructors. Data collection took place through structured interviews with an interview protocol, followed by analysis stages encompassing data collection, reduction, and interpretation. The results discern five overarching themes elucidating the strategies employed in teaching Islamic religious education. Firstly, three schools integrated experiential learning into their pedagogical approach, intertwining it with discussion strategies. Secondly, the application of experiential learning strategies is more straightforward with less intricate subject matter. Thirdly, addressing complex topics necessitates teachers to demonstrate competencies across pedagogical, personal, professional, and social dimensions. Fourthly, not all students readily engage in experiential learning due to unfamiliarity with articulating personal experiences as educational content. Lastly, the study advocates for incorporating advanced methods to tackle complex subject matter. These findings offer a foundational reference for future research endeavors, acknowledging the study's limitations and the recommendations proposed.